Nitrogen availability, water-filled pore space, and N 2 O-N fluxes after biochar application and nitrogen fertilization - Carvalho, Marcia Thais De Melo; Madari, Beata Emoke; Bastiaans, Lammert; van Oort, Pepijn Adrianus Johannes; Leal, Wesley Gabriel de Oliveira; Souza, Diego Mendes de; Santos, Roberto Carlos Gomes dos; Matsushigue, Iva; Maia, Aline de Holanda Nunes; Heinemann, Alexandre Bryan; et al. (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to investigate the impact of the application of wood biochar, combined with N fertilizations, on N2O-N fluxes, nitrogen availability, and water-filled pore space (WFPS) of a clayey Oxisol under rice (wet season) and common bean (dry season) succession. Manual static chambers were used to quantify N2O-N fluxes from soil immediately after a single application of wood biochar (32 Mg ha-1) andafter four crop seasons with N applications (90 kg ha-1 N). Soil ammonium (N-NH4 +) and nitrate (N-NO3-) availability, as well as WFPS, was measured together with N2O-N fluxes. There was no interaction between biochar and N fertilization regarding N2O-N fluxes in any of the four seasons monitored, although these fluxes were clearly enhanced by N applications. At 1.5 and 2.5 years after biochar application, the WFPS decreased. In addition, in the seasons characterized by low WFPS, N2O-N fluxes and soil N-NO3- and N-NH4+ availability were enhanced after N applications. Long-term experiments in the field are important to quantify the impacts of biochar on N2O-N fluxes and to determine the dynamics of these fluxes on soil-related variables.